Après les avoir surveillés, comment faut-il les punir ? - Élie Teicher (Cahiers d’histoire)
Starting in the 1960s, the Belgian gendarmerie renewed its crowd control interventions in response to new forms of protest and the evolving repertoire of actions by protesters. It initiated arrest practices aimed at avoiding massive confrontations. These operations, based on criteria set by the gendarmes, restricted the freedom to protest. They play an important role in the displacement and invisibilization of state violence highlighted by researchers. Moreover, arrests are necessary for potential judicial prosecutions. This article examines the development of these techniques and their effects on the rights of protesters. By studying police conceptions, it shows how arrests have taken on a new role in the coercive system. Then, based on the specific case of the steelworkers' demonstration in March 1982, the article examines how arrests contribute to the shift of state violence by being one of the cogs in the judicial sanction mechanism.